Characteristics of clinical details and endolymphatic hydrops in unilateral and bilateral Ménière's disease in a single Asian group - Shi, Suming; Li, Wenquan; Wang, Dan; Ren, Tongli; Wang, Wuqing (Frontiers in Neurology, 2022)
Objectives: To elucidate the characteristics of the clinical details and endolymphatic hydrops (EH) in bilateral Ménière’s disease (BMD). Methods: A total of 545 patients with definite MD were enrolled. Demographic variables; age of onset; disease course; inner ear function; the coexistence of related disorders such as migraine, delayed MD, drop attacks, and autoimmune diseases; familial history; and characteristics of EH were analyzed. Results: The prevalence of BMD was 15.4%. The disease duration of BMD (84.0 ± 89.6 months) was significantly longer than that of unilateral MD (UMD, 60.1 ± 94.0 months) (P = 0.001). Inner ear functions, evaluated by hearing thresholds and cervical and ocular vestibular evoked myogenic potentials, were more deteriorated in BMD (P < 0.05). The proportions of delayed MD and family history of vertigo were significantly larger in BMD (P < 0.05). EH was observed in 100% of cases on the clinically affected side and 6.1% of cases on the unaffected side. Conclusions: A low prevalence of BMD, longer disease duration, higher frequencies of delayed MD and family history of vertigo in BMD patients are significant findings. All affected ears presented with EH, and a low percentage of unaffected sides presented with EH.